2014
DOI: 10.1097/tme.0000000000000027
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation Team Perceptions of Family Presence During CPR

Abstract: The literature supports family presence during cardiopulmonary resuscitation (CPR) and its many perceived benefits for patients and their families. It also suggests that, overall, health care professionals are supportive of this practice. There have not been any published studies to date that have looked at the perception of family presence from the multidisciplinary resuscitation or code team's perspective. The purpose of this study was to describe the multidisciplinary care provider's understanding and perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 31 publications
(29 reference statements)
0
10
0
2
Order By: Relevance
“…While every effort was made to recruit adequate numbers of all three participant types, ratios were skewed towards RNs. This may reflect a lower level of import placed on FPDR by doctors; a view which is supported by the literature (Zavotsky et al 2014, Porter et al 2015. Low survival rates made recruitment of resuscitation patients difficult, something that has also been noted previously (Mortelmans et al 2010).…”
Section: Strengths and Limitationsmentioning
confidence: 73%
See 1 more Smart Citation
“…While every effort was made to recruit adequate numbers of all three participant types, ratios were skewed towards RNs. This may reflect a lower level of import placed on FPDR by doctors; a view which is supported by the literature (Zavotsky et al 2014, Porter et al 2015. Low survival rates made recruitment of resuscitation patients difficult, something that has also been noted previously (Mortelmans et al 2010).…”
Section: Strengths and Limitationsmentioning
confidence: 73%
“…This may reflect a lower level of import placed on FPDR by doctors; a view which is supported by the literature (Zavotsky et al . , Porter et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the United States showed that, in general, the professionals working in emergency rooms felt that family members should be allowed to stay at the bedside during the service, but there are challenges, including the need for education and theoretical preparation of all health staff to facilitate practical attitudinal changes that promote family stay during the service. 12 In addition to the theoretical preparation, as scored by professionals in this research, it is necessary to adjust the physical structure and work routine in emergency services to enable a suitable hosting of families. These seem to be indispensable elements for the paradigm shift and to overcome the barriers Family centered care in emergency departments Barreto MS, Arruda GO, Garcia-Vivar C, Marcon SS that hinder the implementation of the FCC, for example, the resistance of the practitioners who believe to be restricted to primary health care services this philosophy of care.…”
Section: Discussionmentioning
confidence: 99%
“…8,[10][11][12] In the Brazilian context, FCC is still incipient, has not been implemented in the health services nor discussed in vocational training. This brings up the following question: What is the perception that Brazilian doctors and nurses working in emergency units have about the FCC?…”
Section: Introductionmentioning
confidence: 99%
“…(11,14,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) Outro aspecto evidenciado além da insegurança foi o despreparo profissional que pode ser justificado pela lacuna do CCPF na sua formação; escassez de evidências científicas de alta qualidade; ausência de educação permanente dos profissionais dos serviços de emergência e cuidados intensivos e recursos humanos, materiais e estruturais das unidades que dificultam a permanência da família durante as situações de emergência e procedimentos invasivos. (11,19,30,31,(35)(36)(37)(38)(39)(40)(41)(42) Conclusão A presença da família em procedimentos e em situação de emergências é muito importante, pois contribui direta e indiretamente com a assistência à criança hospitalizada, sendo imprescindível que as instituições de saúde possam instituir filosofia do CCPF e fornecer subsídios para se elaborar protocolos assistenciais, que contemplem as necessidades das famílias, para modificar uma prática ainda centrada no indivíduo e avançar em direção a uma que contemple os princípios centrais do modelo do CCPF. É preciso investir também na educação permanente dos profissionais, a fim de reforçar atitudes, comportamentos e valores que promovam a opção da presença e a parceria com a família nos cuidados com a criança, além da ampliação de pesquisas sobre a presença da família durante os procedimentos invasivos e situações de emergência que possam corroborar, para a prática baseada em evidências científicas.…”
Section: Hegemonia Da Equipe De Saúdeunclassified